2018
DOI: 10.2217/3dp-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Treatment Planning for Heart Interventions using Tissue-Mimicking 3D Printing

Abstract: "The most important contribution of our research was the development and the validation of the novel sensor-enabled tissue-mimicking 3D printed phantom. We have demonstrated the feasibility of manufacturing such a phantom to provide not only an accurate anatomic model but also a benchtop testing platform that gives very important pathophysiologic information regarding the cardiac intervention. "Percutaneous valve treatment has been frequently targeted for 3D printing-guided preprocedural planning. In a recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Dentistry is a field where 3D printing is already starting to make an impact, and this editorial highlights the role of 3D printing in diagnosis, treatment and education in dentistry. Our second-mostread article was an editorial that discussed the role of tissue-mimicking 3D printing in the personalised treatment for cardiovascular problems [2]. Written by Zhen Qian and Mani Vannan, this article concluded that this method of treatment is showing promise and will have an important role in the future.…”
Section: Content Highlightsmentioning
confidence: 99%
“…Dentistry is a field where 3D printing is already starting to make an impact, and this editorial highlights the role of 3D printing in diagnosis, treatment and education in dentistry. Our second-mostread article was an editorial that discussed the role of tissue-mimicking 3D printing in the personalised treatment for cardiovascular problems [2]. Written by Zhen Qian and Mani Vannan, this article concluded that this method of treatment is showing promise and will have an important role in the future.…”
Section: Content Highlightsmentioning
confidence: 99%